DESIGN INTERVENTION AND BRANDING: POSITIONING BAGH PRINTING AS LIFESTYLE STATEMENTS FOR GEN-Z - Srivastava, Nupur; Singh, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Bagh printing, a centuries-old hand block printing tradition from Madhya Pradesh, is renowned for its intricate geometric and floral motifs, natural dyeing techniques, and cultural symbolism. Despite its heritage value and sustainable production methods, the craft faces diminishing demand due to limited product diversification, competition from mass-produced prints, and inadequate branding. This study explores the potential of design intervention and strategic branding to reposition Bagh printing for Gen-Z consumers, whose purchasing behaviour increasingly favours unique, eco-conscious, and culturally rooted products. Through literature review, artisan interviews, and consumer surveys, the research identifies opportunities for contemporary motif adaptation, expanded product lines beyond traditional garments, and incorporation of trend-led colour palettes. Branding strategies—ranging from storytelling and visual identity creation to leveraging social media and e-commerce platforms—are proposed to build a stronger market presence. The paper argues that integrating innovation with authenticity can not only attract younger audiences but also ensure the craft’s economic sustainability and cultural continuity. This approach positions Bagh printing as a relevant, desirable, and globally competitive textile art form in the 21st century.